1993
DOI: 10.1002/aja.1001970103
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluating the role of astrocytes in blood‐brain barrier induction

Abstract: Neural tissue induces brain capillary endothelial cells to express a diverse array of characteristics that allow them to regulate the passage of solutes between the blood and the brain; these features are collectively referred to as the blood-brain barrier (BBB). Because astrocytes are intimately associated with brain capillaries, they have been thought to be the cell type responsible for barrier induction. Widely accepted support of this hypothesis has been derived from experiments showing that astrocytes imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…In particular, in vitro studies of endothelial-astrocytes co-culture model support the idea that astrocytes are essential for the formation of BBB (Holash et al 1993). Direct contact between BMVEC and astrocytes are necessary for optimal tightness of the barrier (Rubin et al 1991), as such, astrocytes end-feet envelop about 99 % of the outer surface of the CNS capillaries (Hawkins and Davis 2005).…”
Section: Discussionmentioning
confidence: 72%
“…In particular, in vitro studies of endothelial-astrocytes co-culture model support the idea that astrocytes are essential for the formation of BBB (Holash et al 1993). Direct contact between BMVEC and astrocytes are necessary for optimal tightness of the barrier (Rubin et al 1991), as such, astrocytes end-feet envelop about 99 % of the outer surface of the CNS capillaries (Hawkins and Davis 2005).…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, culture of brain endothelial cells with astrocytes (Tao-Cheng et al, 1987; Neuhaus et al, 1991) or with astrocyte-conditioned media (Maxwell et al, 1987) has been shown to improve BBB characteristics in vitro. Nonetheless, experiments involving coculture of brain endothelial cells with immature astrocytes have been criticized as inconclusive on methodological grounds, specifically that astrocytes may merely help maintain BBB morphology in culture (Holash et al, 1993). Subsequent in vivo studies have indicated that cerebral microvessels can survive and maintain barrier integrity in areas of the brain that have experienced extensive astrocyte loss (Krum et al, 1997), although these results are in conflict with a more recent study that showed loss and restoration of barrier integrity in vivo following a temporary focal loss of astrocytes (Willis et al, 2004).…”
Section: A Astrocytesmentioning
confidence: 99%
“…The number of mitochondria, M g ¼ 283, for each glial cell was taken from fractional density data. [70][71][72] The spatial distribution of the glial mitochondria was assumed to lie within a sphere around the nucleus as shown in Figure 6(a). The total rate of metabolized oxygen in each tissue cube depended on the number of mitochondria, which in turn is a function of the anisotropic spatial distribution of neurons and glial cells.…”
Section: Tissue Oxygen Diffusion and Metabolismmentioning
confidence: 99%